(untitled) (Research, Society and Development, 2021)
Introduction: Creatine supplementation has been widely used to improve athletic performance. Furthermore, recent discoveries indicate that this supplement has an important therapeutic effect in many diseases characterized by atrophy, muscle weakness and metabolic diseases (muscle, bone, lung and brain). Aim: to analyze through a literature review the effects of chronic use of creatine on kidney function. Methodology: this is an argumentative literature review, based on quantitative descriptive-exploratory technique. The researched samples came from national and international journals, published between the years 2011 and 2021. The journals were acquired from the Scielo and PubMed electronic databases. Results: Several studies, mostly executed on men performing resistance training three times a week, were supplemented with creatine monohydrate at different dosis for 7 days and compared with matched controls supplemented with dextrosol. Several tests were performed, in some of them, blood and urine samples were collected before and 30 days after supplementation in which numerous biochemical parameters and renal function were evaluated. Creatine monohydrate supplementation did not produce adverse events and, as expected, promoted an increase in performance and body weight. Conclusions: the present paper did not find evidence in the literature to support that creatine may represent a risk to the health of healthy men. However, cases in the literature suggest that creatine can harm kidney function with indiscriminate use, so as not to bring health risks, it is recommended that healthy individuals who regularly use this supplement do not exceed 5g/day.